BNN One Stop Service (BOSS): Transformational Leadership and Change Management Lessons - Paritranaya, P.Wiryawan; Martini, Ida Ayu Oka (Universitas Sultan Ageng Tirtayasa, 2025)
This qualitative case study investigates the role of change management and transformational leadership in implementing the BNN One Stop Service (BOSS), an e-government initiative by Indonesia's National Narcotics Agency. Drawing on the STOPE framework, the study analyzes data from interviews, document reviews, and observations at BNN's work units in Bali Province. The findings reveal that successful BOSS implementation requires both strategic leadership direction and comprehensive change management approaches. Key success factors include clear regulations, robust SOPs, effective communication channels, and targeted training programs. While leadership actively monitors implementation progress, collaboration with external stakeholders proves crucial for expanding service reach. However, varying e-readiness levels across work units pose implementation challenges. The study yields significant implications across multiple domains. At the policy level, it suggests developing differentiated implementation frameworks based on organizational readiness. For practitioners, it emphasizes establishing comprehensive change protocols before digital transformation initiatives. Theoretically, it extends the STOPE framework by demonstrating the critical intersection between transformational leadership and change management in e-government implementation. For public sector organizations, the findings indicate that successful digital transformation requires not only technological infrastructure but also leadership commitment, systematic change processes, and sustained stakeholder engagement. These insights particularly benefit developing nations pursuing similar public service digital initiatives.